Interaction of Borrelia burgdorferi Hbb with the p66 promoter - Medrano, Melisa S. (Oxford University Press, 2010)
Borrelia burgdorferi, an agent of Lyme disease, encodes the β(3)-chain integrin ligand P66. P66 is expressed by B. burgdorferi in the mammal, in laboratory media, and as the bacteria are acquired or transmitted by the tick, but is not expressed by the bacterium in unfed ticks. Attempts to reveal factors influencing expression revealed that P66 was expressed in all in vitro conditions investigated. Candidate regulators identified in a search of the B. burgdorferi genome for homologs to other bacterial transcription factors were cloned and introduced into E. coli carrying a p66 promoter-signal sequence-phoA (alkaline phosphatase, or AP) fusion. Three candidate transcription factors—two that decreased AP activity (Hbb and BB0527), and one that increased AP activity (BBA23)—were identified. BBA23 and BB0527 did not bind to the p66 promoter at physiologically relevant concentrations. In contrast, several promoter fragments, including p66, were bound by Hbb (BB0232), with slightly different affinities. Consistent with results from other laboratories, Hbb appears to recognize multiple DNA sequences. Changes in the expression of p66 and bb0232 in the tick at various points with respect to feeding on mice, along with the results of the reporter experiment in the surrogate host E. coli, are consistent with Hbb/BB0232 being involved in regulating p66 expression.